2015
DOI: 10.2527/jas.2014-8695
|View full text |Cite
|
Sign up to set email alerts
|

Effect of castration timing and oral meloxicam administration on growth performance, inflammation, behavior, and carcass quality of beef calves12

Abstract: Beef bull calves (n = 62) were assigned randomly, within sire breed, to 1 of 4 treatments at birth. Treatments were 1) surgical castration near birth, 2) surgical castration near birth with oral administration of meloxicam (1 mg/kg BW), 3) surgical castration at weaning (WNG), or 4) surgical castration at weaning with oral administration of meloxicam (1 mg/kg BW; WMX). A subset of calves (n = 7/treatment group) were selected randomly near birth for blood collection, behavioral analyses, and rectal temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 20 publications
5
19
1
2
Order By: Relevance
“…The lack of medication effect on APP concentrations in this study was similar to the findings of Brown et al (2015), who reported no differences in Hp concentrations when new born calves were castrated with or without the administration of oral meloxicam. In contrast, in the same study conducted by Brown et al (2015), as well as a study by Roberts et al (2015), it was found that oral meloxicam reduced peak Hp concentrations in calves castrated at weaning. Roberts et al (2018) observed that the reduction of Hp concentrations after oral meloxicam administration was only visible after surgical castration vs. band castration in weaned beef calves.…”
Section: Resultssupporting
confidence: 90%
“…The lack of medication effect on APP concentrations in this study was similar to the findings of Brown et al (2015), who reported no differences in Hp concentrations when new born calves were castrated with or without the administration of oral meloxicam. In contrast, in the same study conducted by Brown et al (2015), as well as a study by Roberts et al (2015), it was found that oral meloxicam reduced peak Hp concentrations in calves castrated at weaning. Roberts et al (2018) observed that the reduction of Hp concentrations after oral meloxicam administration was only visible after surgical castration vs. band castration in weaned beef calves.…”
Section: Resultssupporting
confidence: 90%
“…For example, Meléndez et al (2018b) observed that SAA concentrations were elevated during the first 3 d after castration and branding were conducted. Brown et al (2015) found differences in Hp up to 72 h post castration and Warnock et al (2012) up to day 6 post castration in weaned calves.…”
Section: Itemsmentioning
confidence: 71%
“…Meloxicam is a nonsteroidal anti-inflammatory drug (NSAID) that has been recently tested to mitigate the pain of castration in weaned calves (Brown et al 2015;Roberts et al 2015;Meléndez et al 2017b). Furthermore, the anti-inflammatory properties of oral meloxicam have been shown to reduce morbidity in weaned castrated beef calves suggesting that its effect may last several days after a single treatment (Coetzee et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Castration is known to be a painful and acute stressor (Stafford et al 2002;Brown et al 2015), and has been used as an applicable model of stress to better understand the cortisol response to acute stress (Earley and Crowe 2002). Following surgical castration of bull calves behavioural pain measures remain elevated for up to 3 d (Olson et al 2016); however, the full duration of time pain persists following castration is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The number of steps taken by calves as well as their stride length decreases following castration in calves castrated without pain medication (Currah et al 2009). In addition, abnormal postures, including statue standing, increase following castration to decrease the stimulation of the injured site (Molony et al 1995) and standing time can be measured using accelerometers (White et al 2008;Brown et al 2015). Thus, accelerometers were used in this study to determine lying and standing time as a behavioural measure of postcastration pain (Brown et al 2015).…”
Section: Discussionmentioning
confidence: 99%